Possibility of Undifferentiated Human Thigh Adipose Stem Cells Differentiating into Functional Hepatocytes - Jong Hoon Lee; Kuk Han Lee; Min Ho Kim; Jun Pyo Kim; Seung Jae Lee; Jinah Yoon (Archives of Plastic Surgery, 2012)
Background This study aimed to investigate the possibility of isolating mesenchymal stem cells (MSCs) from human thigh adipose tissue and the ability of human thigh adipose stem cells (HTASCs) to differentiate into hepatocytes. Methods The adipose-derived stem cells (ADSCs) were isolated from thigh adipose tissue. Growth factors, cytokines, and hormones were added to the collagen coated dishes to induce the undifferentiated HTASCs to differentiate into hepatocyte-like cells. To confirm the experimental results, the expression of hepatocyte-specific markers on undifferentiated and differentiated HTASCs was analyzed using reverse transcription polymerase chain reaction and immunocytochemical staining. Differentiation efficiency was evaluated using functional tests such as periodic acid schiff (PAS) staining and detection of the albumin secretion level using enzyme-linked immunosorbent assay (ELISA). Results The majority of the undifferentiated HTASCs were changed into a more polygonal shape showing tight interactions between the cells. The differentiated HTASCs up-regulated mRNA of hepatocyte markers. Immunocytochemical analysis showed that they were intensely stained with anti-albumin antibody compared with undifferentiated HTASCs. PAS staining showed that HTASCs submitted to the hepatocyte differentiation protocol were able to more specifically store glycogen than undifferentiated HTASCs, displaying a purple color in the cytoplasm of the differentiated HTASCs. ELISA analyses showed that differentiated HTASCs could secrete albumin, which is one of the hepatocyte markers. Conclusions MSCs were islolated from human thigh adipose tissue differentiate to heapatocytes. The source of ADSCs is not only abundant abdominal adipose tissue, but also thigh adipose tissue for cell therapy in liver regeneration and tissue regeneration.